The faith based organization response to HIV/AIDS : a case study of the JL Zwane Memorial Church in Guguletu, Cape Town - Xapile, Nobis Bridget Zethu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.